Soil Conservation Practices and Stakeholder’s Participation in Research Projects—Empirical Evidence from Southern Italy - Rosanna Salvia; Rosaria Simone; Luca Salvati; Giovanni Quaranta (Agriculture, 2018)
Adoption of soil conservation practices is promoted by increased engagement between researchers and stakeholders. By reporting a case study from southern Italy where farmers have been involved in research projects dealing with soil conservation over several years, we demonstrated that the rate of adoption of conservative technologies is positively linked to the degree of stakeholder participation in the project and that farmers (and other stakeholders) have been driven toward more conscious perception of the complex link between agricultural practices, environmental impacts and socioeconomic effects. The results of this study reinforce the pivotal role of effective participatory processes in soil conservation—evidencing the importance of (i) time required to build relationships and (ii) intensity (and persistence) of collaboration among similar initiatives. Empirical evidence highlights the need to combine different approaches to deal with soil degradation. As well as the participatory time length, the synergies between the methods utilized, and the range of interacting mind sets are also very important.